2023
DOI: 10.3390/nu15153313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unripe Black Raspberry Extract Supplementation on Male Climacteric Syndrome and Voiding Dysfunction: A Pilot, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Male climacteric syndrome (MCS) is a medical condition that can affect middle-aged men whose testosterone levels begin to decline considerably. These symptoms may include fatigue, decreased libido, mood swings, and disturbed sleep. MCS can be managed with lifestyle modifications and testosterone replacement. However, testosterone therapy may cause number of side effects, including an increased risk of cardiovascular issues. This study aims to evaluate the efficacy and safety of unripe black raspberry extract (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 40 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…For evaluating the 16 studies, it was necessary to read their full text, which led to the exclusion of five studies due to having no RCT design ( n = 1), combination therapy ( n = 3), and lack of a control group ( n = 1). Finally, 11 studies (13 arms) with 512 participants were eligible to be included in this meta‐analysis (An et al., 2016 ; Cho et al., 2020 ; Franck et al., 2020 ; Franck et al., 2022 ; Jeong, Hong, et al., 2016 ; Jeong et al., 2014 ; Jeong, Kim, et al., 2016 ; Jung et al., 2023 ; Mosah et al., 2015 ; Park et al., 2015 ; Schell et al., 2019 ) (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For evaluating the 16 studies, it was necessary to read their full text, which led to the exclusion of five studies due to having no RCT design ( n = 1), combination therapy ( n = 3), and lack of a control group ( n = 1). Finally, 11 studies (13 arms) with 512 participants were eligible to be included in this meta‐analysis (An et al., 2016 ; Cho et al., 2020 ; Franck et al., 2020 ; Franck et al., 2022 ; Jeong, Hong, et al., 2016 ; Jeong et al., 2014 ; Jeong, Kim, et al., 2016 ; Jung et al., 2023 ; Mosah et al., 2015 ; Park et al., 2015 ; Schell et al., 2019 ) (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, complaints of fatigue, skin rash, and abdominal pain were reported even in the placebo control group. In another study conducted by Jung et al (2023), although the relationship between intervention and complaint was ruled out, complications including oral leukoplakia, heartburn, elevated T-PSA, upper respiratory infection, and dysuria were reported in the group receiving black raspberry extract. Abbreviations: L, Low; H, High; U, Unclear.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations